2017
DOI: 10.1002/em.22147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluoride on morphology, growth, development, and thyroid hormone of Chinese toad (Bufo gargarizans) embryos

Abstract: Excessive fluoride in natural water ecosystem has the potential to detrimentally affect amphibians, but little is known of such effects or underlying mechanisms in Bufo gargarizans embryos. In the present study, the effects of fluoride exposure on B. gargarizans embryos were investigated. First, fluoride teratogenic experiment showed that the 9 days EC of fluoride on B. gargarizans embryos was 177.62 mg/L. Then, we studied the sublethal effects of fluoride on B. gargarizans embryos at control, 0.7, 4.1, 19.6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
5
0
3
Order By: Relevance
“…Our results showed that the total length of tadpoles of B. cordobae was not influenced by the larval stage. Therefore, the shortest total length recorded in larvae of the HF-CN stream could be due to high concentrations of fluoride, due to is a sensitive parameter a the effects of fluoride (Goh and Neff, 2003; Zhao et al., 2013; Chai et al., 2017; Pollo et al., 2016; Zhang et al., 2018). For example, Chai et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results showed that the total length of tadpoles of B. cordobae was not influenced by the larval stage. Therefore, the shortest total length recorded in larvae of the HF-CN stream could be due to high concentrations of fluoride, due to is a sensitive parameter a the effects of fluoride (Goh and Neff, 2003; Zhao et al., 2013; Chai et al., 2017; Pollo et al., 2016; Zhang et al., 2018). For example, Chai et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) found that total length of embryo of Rana chensinensis (Chordata, Ranidae) decreases with increasing levels of fluoride (≥0.7 mg F/L). The specific mechanism of inhibition may be the accumulation of fluoride in the body, which causes an imbalance in bone deposition and the remodeling activities that lead to skeletal fluorosis (Zhang et al., 2018). In addition, the metamorphosis of the tadpoles is delayed in the presence of high concentrations of fluoride (Chai et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations